ChemInform Abstract: Synthesis of Dihydroquinoxaline‐2(1H)‐ones via Palladium‐Catalyzed Intramolecular C—N Bond Formation. Issue 46 (October 2016) - Areephong, Jetsuda; Huo, Bright; Mbaezue, Ifenna I.; Ylijoki, Kai E. O.
Abstract: The cyclization reaction does not display significant substitution dependence, proceeding well for both alkyl and aryl substituted substrates.